Applying colloidal silica suspensions injection and sequential gelation to block vertical water flow in well annulus: laboratory testing on rheology, gelation, and injection - Zhong, Lirong; Mackley, Rob; Li, Lan; Thomle, Jon; Day-Lewis, Fred; Saslow, Sarah (Frontiers in Environmental Science, 2024)
We evaluated the application of silica suspension injection and sequential gelation to block vertical water flow in the annuli of long-screened wells. First, we studied the viscosity, rheological behavior, and gelation performance of colloidal silica suspensions in batch tests.Then, we tested the injection of silica suspensions and the water flow blocking efficiency of the later formed silica gel in column and bench-scale sandbox experiments. Micron-sized fumed powder silica suspensions and nanosized silica suspensions recovered from geothermal fluids were tested in this work. Fumed silica suspensions showed shear thinning, while nanosized silica suspensions exhibited Newtonian flow behavior. During the gelation process, the nanosized silica suspension changed from a Newtonian fluid to a shear thinning fluid while increasing its overall viscosity. At comparable concentrations, the nanosized silica suspensions have much lower viscosity than that of the fumed silica suspensions. Increases in the Na + concentration and silica particle concentration in these suspensions shortened the gelation time. Silica suspension gelation in sand columns completely blocked the water flow and sustained the injection pressure up to 50 psig (344.7 kPa). A silica suspension was successfully injected into the target zone in the annulus of a bench-scale sandbox mimicking long-screened wells in the field. The silica gel formed in the annulus effectively blocked chemical transport through the gelled zone. Our research reveals that a process using silica suspension injection and sequential gelation technology is promising for blocking the vertical water flow and chemical transport through the filter pack in targeted zones within the annulus of longscreened well systems.